The iconic images of the Philippine press identification card in Metro Manila - Evidente, Shirley Palileo (2009)
The media have been bestowed power that earns them either public trust or the ire of the government. Considered the fourth estate, they have been integrated into the institutional system of checks and balances. The press ID represents the people behind the media and their power. This study then identifies the iconic images of the Press ID and the factors, circumstances, or situations that have led to the formation of that iconic image. Conducted in Metro Manila, research findings show that the Press ID has served purposes other than identification. These other uses and attributes were categorized into prestige, material or economic, safety and convenience, and functional purposes.